Pemerian alam sebagai simbol femininitas dalam novel Hana wo Hakobu Imouto - Rahwati, Wawat (Japanese Research on Linguistics, Literature, and Culture, 2018)
This paper discusses about interconnecting nature an women in one of Japanese literary work named Hana wo Hakobu Imouto by Natsuki Ikezawa. He has written numerous novels and through his works such as Hana wo Hakobu Imouto, he depicts upon the relationship between nature and women. through this novel i assume nature can be seen as a representation about femininity and has interconnection with women. According to my assumption, i analyze this novel by employing the culture eco-feminism perspective to aim at showing how nature can be represented as a symbol of femininity through portraying the women characters and the setting of place of the story in this novel. The result is found that the water and iearth as nature elements which have been portrayed dominanly in every setting of places in the story, The water is represended across by river in Paris, rain in Thailand, and sea in Bali show a symbol as a 'mother's womb' called fetus which is very important to protect for someone's life. Meanwhile the earth is representing through rice fields show a symbol of femininity which represent of mother's nurture who protect someone's life.Keyword: cultural eco-feminism, femininity, Hana wo Hakobu Imouto, nature